Dopant‐Free and Green‐Solvent‐Processable Hole‐Transporting Materials for Highly Efficient Inverted Planar Perovskite Solar Cells. Issue 10 (6th October 2020) - Meng, Fei; Wang, Yunhao; Wen, Yaping; Lai, Xue; Li, Wenhui; Kyaw, Aung Ko Ko; Zhang, Ren; Fan, Dongyu; Li, Yuheng; Du, Mengzhen; Guo, Xiao; Ma, Haibo; et al.
Abstract : Hole‐Transporting Materials In article number 2000327, Aung Ko Ko Kyaw, Haibo Ma, Gongqiang Li, and co‐workers synthesize and systemically characterize saddle‐shaped small molecules α, β‐COTh‐Ph‐OMeTAD and β, β‐COTh‐Ph‐OMeTAD as dopant‐free hole‐transporting materials (HTMs) in inverted perovskite solar cells (i‐PSCs). High power conversion efficiencies (PCEs) (17.59% and 18.53%) and stable‐enhanced PSCs devices are achieved, and more than 80% of the maximum PCE is retained after storing in glove box for 150 days.